Assessment of math learning by the Early Mathematical Competence Test Spanish version. (European Journal of Education and Psychology, 2009)
The Early Mathematical Competence Test (EMTC) assesses mathematical knowledge for kindergarden and primary school children. The test has 3 versions, of 40 items each and measures eight aspects of mathematical competence: Concepts of comparison; Classification; Correspondence; Seriation; Using counting words, forwards and backwards; Structures counting; Resultative counting; and General knowledge of numbers. Each subtest has five questions and a total score of 40 points. The main aim of this study was the standardization of EMTC for a Spanish population, following the international reliability and validation statistical rules. The test was administered to 1053 participants aged 4 to 7 (539 male and 514 female) from 14 schools. The EMTC provides a Mathematical Competence index, has a standard prediction value, and validation and reliability scores were significant.Key words: Early math, cognition, assessment, number sense, kindergarden, primary school.